2019
DOI: 10.1002/adom.201901003
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Exciton Polaritons in Layered Transition‐Metal Dichalcogenides

Abstract: Exciton polaritons (EPs) are half‐light, half‐matter quasiparticles formed due to the coupling between photons and excitons in semiconductors. Their uniqueness lies at the strong light–matter interactions and long‐distance transport, thus promising for many novel applications in photonics, information, and quantum technologies. Recently, EPs in group‐VI transition‐metal dichalcogenides (TMDs) have attracted a lot of research interest due to their room‐temperature stability, long‐distance propagation, and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 140 publications
(264 reference statements)
0
57
0
Order By: Relevance
“…A diagonal permittivity tensor can describe it with two optical constants corresponding to the crystallographic ab-plane and the c-axis 16 . Interestingly, these anisotropic properties of TMDCs were qualitatively demonstrated back in 1967 by Liang et al 17 , but only currently attracted significant importance in experiments dealing with novel regimes of light-matter interactions 18,19 comprising exciton-polariton transport 20 , Zenneck surface waves 21 , tunable modal birefringence 22 , and anapole-exciton polaritons 23 . Although a recent pioneering work by Hu et al 16 reported a birefringence value of Δn = 1.4 for MoS 2 at λ = 1530 nm, the values of asymmetric dielectric responses of MoS 2 in a wide wavelength interval have so far remained unknown.…”
mentioning
confidence: 97%
“…A diagonal permittivity tensor can describe it with two optical constants corresponding to the crystallographic ab-plane and the c-axis 16 . Interestingly, these anisotropic properties of TMDCs were qualitatively demonstrated back in 1967 by Liang et al 17 , but only currently attracted significant importance in experiments dealing with novel regimes of light-matter interactions 18,19 comprising exciton-polariton transport 20 , Zenneck surface waves 21 , tunable modal birefringence 22 , and anapole-exciton polaritons 23 . Although a recent pioneering work by Hu et al 16 reported a birefringence value of Δn = 1.4 for MoS 2 at λ = 1530 nm, the values of asymmetric dielectric responses of MoS 2 in a wide wavelength interval have so far remained unknown.…”
mentioning
confidence: 97%
“…resulting in interesting phenomena such as excitonic laser [12][13][14][15][16][17] and exciton-polariton [18][19][20][21][22][23]. Additionally, the coupling between an optical signal and carrier valley can also be controlled by an external electric field [9,24,25], magnetic field [26][27][28][29][30][31][32][33], and strain [34].…”
Section: Introductionmentioning
confidence: 99%
“…The control of light–matter interactions at the nanoscopic scale is fundamental to many contemporary scientific disciplines. [ 1–6 ] Among the related research fields in which new interest has arisen, the study of the interactions between quantum emitters and optical cavities in particular is driving considerable research activity. [ 7–14 ] These interactions fall into two distinct regimes, referred to as weak and strong coupling.…”
Section: Introductionmentioning
confidence: 99%